2019
DOI: 10.1021/acsenergylett.9b02272
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Phase Evolution in DMAI-Derived Inorganic Perovskite Solar Cells

Abstract: Inorganic CsPbI 3 is promising to enhance the thermal stability of perovskite solar cells. The dimethylamine iodide (DMAI) derived method is currently the most efficient way to achieve high efficiency, but the effect of DMAI has not been fully explained. Herein, the chemical composition and phase evolution of the mixed DMAI/CsPbI 3 layer during thermal treatment has been studied. The results demonstrate that, with the common DMAI/CsI/PbI 2 recipe in DMSO solvent, a mixed perovskite DMA 0.15 Cs 0.85 PbI 3 is fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 44 publications
1
127
0
Order By: Relevance
“…By integrating the organic cation dimethylammonium (DMA + ) into the precursor solution of CsPbI 3 perovskite, crystallization of the tetragonal ( β ) phase of CsPbI 3 perovskite can be improved, and the phase better stabilized . DMA + in CsPbI 3 would beneficially increase the Goldschmidt tolerance factor, however, whether it remains in the resultant film is still debated and is likely annealing temperature‐dependent . An alternative strategy to achieve stability is through halide alloying with bromide in CsPbI 3 − x Br x compositions, which has the further advantage of optical bandgap tenability across a range of phase‐stable perovskite compositions (in an inert atmosphere at room temperature) .…”
Section: Introductionmentioning
confidence: 99%
“…By integrating the organic cation dimethylammonium (DMA + ) into the precursor solution of CsPbI 3 perovskite, crystallization of the tetragonal ( β ) phase of CsPbI 3 perovskite can be improved, and the phase better stabilized . DMA + in CsPbI 3 would beneficially increase the Goldschmidt tolerance factor, however, whether it remains in the resultant film is still debated and is likely annealing temperature‐dependent . An alternative strategy to achieve stability is through halide alloying with bromide in CsPbI 3 − x Br x compositions, which has the further advantage of optical bandgap tenability across a range of phase‐stable perovskite compositions (in an inert atmosphere at room temperature) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several works suggested that the CsPbI 3 inorganic perovskite fabricated by the HPbI 3 method may lead to the formation of the hybrid perovskite of Cs 1− x DMA x PbI 3 . [ 55–57 ] However, the UV–vis absorbance spectra of these Cs 1− x DMA x PbI 3 with different claimed DMA contents are similar to each other. Recently, Wang et al.…”
Section: Solution Chemistry Preparation Of Cspbi3 Inorganic Perovskitementioning
confidence: 77%
“…Finally, the device with HI delivered a high PCE of 17.3%. As the intermediate phase was DMAPbI 3 or DMAI/DMAPbI x after HI was introduced, Pang and coworkers [77] directly incorporated DMAI into CsPbI 3 precursor solution to prepare phase-stable and high-quality perovskite films. As shown in Figure 10a, it was revealed that DMAPbI 3 and Cs 4 PbI 6 were first formed when films were annealed at 100 C for 10 min and then converted into mixed-cation perovskite phase DMA 0. was directly transformed into γ-CsPbI 3 and then was spontaneously converted into δ-CsPbI 3 .…”
Section: Organic Cationsmentioning
confidence: 99%
“…However, the influence mechanism of DMAI residue for device stability was not revealed in this work, which remains investigated deeply in the subsequent research work. Although huge progresses have been achieved on DMAI, inconsistent conclusions were obtained on its role of DMAI as an additive [12,22,117] or dopant, [77,109] which could be ascribed to different annealing temperatures and times along with different amounts of DMAI and preparation condition (e.g., humidity, oxygen, etc. ).…”
Section: Organic Cationsmentioning
confidence: 99%